2015
DOI: 10.1007/s10661-014-4167-x
|View full text |Cite
|
Sign up to set email alerts
|

Total coliforms, arsenic and cadmium exposure through drinking water in the Western Region of Ghana: application of multivariate statistical technique to groundwater quality

Abstract: In recent times, surface water resource in the Western Region of Ghana has been found to be inadequate in supply and polluted by various anthropogenic activities. As a result of these problems, the demand for groundwater by the human populations in the peri-urban communities for domestic, municipal and irrigation purposes has increased without prior knowledge of its water quality. Water samples were collected from 14 public hand-dug wells during the rainy season in 2013 and investigated for total coliforms, Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(136 citation statements)
references
References 74 publications
7
129
0
Order By: Relevance
“…Also, 6.14 to 7.50 pH units for pH, 48 to 240 mg/l for total alkalinity, 80.10 to 524 mg/l for TDS and 131 to 873 μS/cm for electrical conductivity. Affum et al (2015) reported toxic elements, hardness and salinity pollution as the main factors affecting the quality of groundwater. Mineral dissolution, cation exchange and silicate weathering influenced the quality of groundwater.…”
Section: Chemical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 6.14 to 7.50 pH units for pH, 48 to 240 mg/l for total alkalinity, 80.10 to 524 mg/l for TDS and 131 to 873 μS/cm for electrical conductivity. Affum et al (2015) reported toxic elements, hardness and salinity pollution as the main factors affecting the quality of groundwater. Mineral dissolution, cation exchange and silicate weathering influenced the quality of groundwater.…”
Section: Chemical Variablesmentioning
confidence: 99%
“…Affum et al (2015) reported the absence of E. coli in the water sampled, but wells contained total coliforms (Enterobacter species) that was 36%. All but one of the hand-dug wells and boreholes showed faecal contamination with levels above WHO and GSA guidelines.…”
Section: Biological Variables Of Water Resourcesmentioning
confidence: 99%
“…In the assumption FA reduces contribution of less relevant variables obtained during the extraction of data by the PCA. The main difference between the PCA and FA is that the FA allows the expression of the measured values as a combination of factors and the equation includes a term, and thus obtained varifactors (factors after varimax rotation) may comprise previously unobservable hidden variables [18,20,30,31,35,36].…”
Section: Methodsmentioning
confidence: 99%
“…Chemometric procedures were often used for conducting studies on the quality of natural waters -including lake water [18][19][20][21][22][23][24]. Most of the works is a study of river waters in the catchment [25][26][27][28][29][30][31][32][33], as well as groundwater [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the level of human activity in a place, the higher the level of household waste produced and if not properly managed, this can cause a decrease in groundwater quality (Takem et al, 2009;Bahar et al, 2010;Rani and Sasidhar, 2010;Akoteyon et al, 2011;Hastuti and Wardiha 2012;Strohschön et al, 2012;Affum et al, 2015). The sewage channel is the main cause of water contamination in Jakarta.…”
Section: Introductionmentioning
confidence: 99%